2011
DOI: 10.1210/jc.2011-0162
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Bone Turnover in Gaucher Disease: Modeling the Evolution of Bone Disease

Abstract: In contrast to earlier hypotheses, we propose that in GD patients, primarily a decrease in bone formation causes an imbalance in bone remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 46 publications
3
39
1
1
Order By: Relevance
“…Bone turnover can be measured with specific biochemical markers [60] for enzyme activities, the release of various structural components of bone, and proteins involved in the processes of bone formation (Table 5). Over the years, most of these parameters have been tested in patients with GD [33][34][35][36][37][38][39][40]. Urinary total hydroxyproline levels are used to identify osteoclastic hyperactivity.…”
Section: Biomarkers For Bone Damagementioning
confidence: 99%
“…Bone turnover can be measured with specific biochemical markers [60] for enzyme activities, the release of various structural components of bone, and proteins involved in the processes of bone formation (Table 5). Over the years, most of these parameters have been tested in patients with GD [33][34][35][36][37][38][39][40]. Urinary total hydroxyproline levels are used to identify osteoclastic hyperactivity.…”
Section: Biomarkers For Bone Damagementioning
confidence: 99%
“…Markers of bone formation in treatment-naïve patients appeared to be normal or decreased, whereas markers of bone degradation were mainly normal or increased [45,46,48]. According to this finding, Stowens DW et al [47] reported a decrease in bone resorption on seven patients who underwent bone biopsies.…”
Section: Bone Metabolism and Biochemical Markers In Gdmentioning
confidence: 92%
“…A study measured serum osteocalcin (OC), a marker of bone formation, and type I collagen C-terminal telopeptide (ICTP), a marker of bone resorption, in 16 patients with type 1 GD and in 29 agematched controls, and the results indicated a significant decrease of both OC and ICTP values in patients with GD compared to the unaffected controls [46]. Recently, Van Dussen et al found that OC was decreased in 50 % of 40 type 1 GD patients with no significant change in ICTP and N-terminal propeptide of type 1 procollagen (PINP) and concluded that imbalances in bone turnover result primarily from a decrease in bone formation [48]. In addition, OC concentration was negatively correlated to measures of overall disease severity and positively correlated with imaging data, suggesting a relation with disease severity [48].…”
Section: Bone Metabolism and Biochemical Markers In Gdmentioning
confidence: 98%
See 2 more Smart Citations